The making of Turkey's 2018-2019 economic crisis - Ümit Akcay; Ali Riza Güngen (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
Turkish economic growth depends on capital inflows and access to cheap credit sources. Once the global financial conditions tightened in 2018, Turkey was among the emerging markets that suffered the most. This article analyses the making of Turkey's economic crisis in 2018-2019, while elaborating the phases of Turkish financialisation. It locates the slow-motion drift of Turkish economy within the context of dependent financialisation and argues that a long-term account is needed to grasp the economic turmoil of recent years.
Keywords: E44; E52; E6; F31; G01; 330; Turkey; Dependent Financialisation; Economic Crises; Crisis Management